Openness to Experience and Entrepreneurial Intentions: A Mediating Role of Creative Problem-Solving among Students in Ludhiana - Ms. Kajal Juneja (Journal of Advanced Research in Economics and Business Management, 2024)
This study investigates the relationship between openness to experience and entrepreneurial intentions among students, exploring the mediating role of creative problem-solving. Building on the Big Five personality framework and creativity research, we assume that individuals high in openness will exhibit stronger entrepreneurial intentions due to their enhanced creative problem-solving abilities. The study employs a quantitative research design with survey data collected from a sample of university students. The analysis utilizes structural equation modelling to examine the proposed relationships. We anticipate findings that support the mediating role of creative problem-solving, shedding light on the underlying mechanism through which openness to experience influences entrepreneurial aspirations. Our research contributes to the understanding of personality traits and individual differences in entrepreneurial intention, informing potential interventions and support programs to foster entrepreneurial spirit and equip students with the necessary skills for venturesome endeavours.